IN VITRO STUDIES ON THE SYNERGISTIC EFFECT OF MORINDA CITRIFOLIA L. (NONI) AND METHOTREXATE ON CYTOTOXICITY OF HELA CELL LINES - MHATRE BHAKTI,; MARAR THANKAMANI, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Cancer remains to be one of the leading causes of death around the world. Modern targeted therapies have undeniably improved cancer patients’ survival, but search still continues for safer and more effective drugs. This work is an attempt to assess the effectiveness of cotreatment of aqueous fruit extract of Morinda citrifolia L. (Noni) on methotrexate (MTX)-induced cytotoxicity on HeLa cancer cell line. Methods: HeLa cells were treated with different concentrations of MTX and Noni alone and in combination for 24 and 48 h and studied for the cytotoxic effects by various approaches. Results: There was a dose-dependent inhibition of growth when treated with MTX in a dose range of 0.045–45.4 μg/ml and Noni for a dose range of 0.3–30 mg/ml for 48 h. The IC50 for MTX was 4.45 μg/ml (1 μM/ml), and for Noni, it was 8 mg/ml while the combination exhibited a more intensive growth inhibitory effect. Our results were confirmed with phase-contrast microscopy, whereby the number of viable cells decreased with an increase in the concentration of Noni. Cells were found to have rounded up and detached from the flask indicating apoptosis. Apoptosis in HeLa cell lines was further confirmed by DNA fragmentation and flow cytometry. Conclusion: It can be concluded that Noni may enhance MTX cytotoxicity by inducing apoptosis and cell cycle arrest. Hence, cotreatment with Noni may reduce the dosage of MTX necessary for inhibiting proliferation of malignant cells and hence decrease the toxic effects of MTX on the system.